PENINGKATAN LOYALITAS MELALUI LOKASI DAN KEANEKARAGAMAN BARANG - MARNO NUGROHO; RATIH PARAMITA (Jurnal Ekonomi dan Bisnis, 2009)
This study proposed to examine the influence of location and product diversity on spent decisionto consumer’s loyality. The study was taken place at Carrefour, one of hypermarket in Semarang.This is an explanatory research. The number of sample of the research is 105 consumersthe method reseacrh with accidental sampling method. Questionnaire was used to obtain thedata. Stuctural Equation Modelling (SEM) was applied to prove and examine the hypotheses.Result of the study showed that location positively affect the Research begun since spent decision.Product diversity also positively affect (Purchasing decision and finally, purchase decisionpositively affect consumer’s loyality.Keywords : Location, product diversity, purchasing decision, loyality